The Influence of Green Marketing on Customer Loyalty Through Customer Satisfaction as an Intervening Variable (Case Study on Cafe Sudut Temu in Slawi) - Firda Fiah Zaini; Syariefful Ikhwan; Ari Kristiana; Dumadi Dumadi; Roby Setiadi (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to examine the effect of green product, green price, green promotion, and green place on customer loyalty, with customer satisfaction as an intervening variable at Cafe Angle Temu in Slawi. The study uses a descriptive quantitative method with Structural Equation Modeling (SEM) analysis assisted by AMOS software. The total number of respondents was 437 customers of Cafe Corner Temu in Slawi. The results indicate that green promotion has a positive effect on customer satisfaction, with a CR value of 6.045 (CR ≥ 1.96) and p = 0.000 (p ≤ 0.05). In contrast, green product does not significantly affect customer satisfaction (CR = -0.505, p = 0.614), green price has no effect (CR = -0.233, p = 0.816), and green place is also not significant (CR = 1.908, p = 0.056). Regarding the path to customer loyalty, green place has a positive effect on customer loyalty (CR = 8.827, p = 0.000). Meanwhile, green product (CR = 0.002; p = 0.998), green price (CR = 1.528; p = 0.126), green promotion (CR = -1.518; p = 0.129), and customer satisfaction (CR = 0.426; p = 0.670) do not show a positive effect on customer loyalty.